MT BB: tomato cultivar for practical classes of plant genetics and breeding - Piotto,Fernando Angelo (2013)
MT BB cultivar originated from a backcross program which aimed at adding two recessive mutations that alter leaf architecture (potato leaf - c) and flower color (white flower - wf) to Micro-Tom cultivar, which is a tomato miniature. MT BB was developed for use in practical classes of genetics and breeding in both undergraduate and graduate courses.